State of the art thermal energy storage solutions for high performance buildings - Cao, Sunliang (2010)
In this thesis, the general thermal energy storage solutions for high performance buildings have been comprehensively reviewed. Based on the properties of storage material, the thermal storage solutions can be classified into sensible, latent and thermochemical heat storages. Their categories, characteristics and certain applications have been systematically introduced. Special emphases are put on the latent thermal storage technologies. Different classifications of phase change materials (PCMs), i.e. organic-, inorganic-, and eutectic- PCMs, have been carefully presented with their particular features and material candidates. PCM applications can cover almost every part of the building envelopes, such as wall, floor, ceiling, roof, window and sunshading systems. They can function either as a thermal buffer to alleviate the exterior environmental influences, or as an “automatic” indoor temperature regulator to attenuate the indoor temperature fluctuations and improve the thermal comfort. An experimental work conducted by me in NTNU/SINTEF Building and Infrastructure’s Laboratory has also been presented, analysed and discussed in this thesis. The laboratory work focused on the PCM integrated wall with the purpose to investigate the influences caused by convective conditions and attachment of PCM layer: their influences on the temperatures, heat fluxes, stratifications (temperature and heat flux), energy storage effect, heat conductive loss, convection coefficient, and energy saving effect will be carefully compared and analysed in this thesis. The much enhanced energy storage and release effects by attachment of PCM layer during phase change processes resulted in a less fluctuated interior environment and much significant energy saving effect. Meanwhile, the interior convective conditions would influence the foregoing effects caused by attachment of PCM layer, thus the best optimization of PCM layer and convective conditions should be based on the analysis of thermal comfort zone under certain conditions in room environment.